Histomorphological Changes in Placentae of Pre-Eclamptic Mothers with Reference to Number of Villous Capillaries - IfraSaeed, SamiaSarwar Musharaf Baig , Iram Iqbal (Journal of Rawalpindi Medical College, 2014)
Background: To study the histomorphological changes in placentae of pre-eclamptic mothers and to compare them with placentae of normotensive mothers with reference to number of villous capillaries. Methods: In this comparative study, one hundred placentae were divided into two groups. Normotensive (N) group included placentae from mothers having normal blood pressure and Hypertensive (H) group included placentae from mothers having pre-eclampsia. After fixation the placentae were divided into four quadrants and 5mm tissue was taken from the center of upper right and lower left quadrants. After tissue processing and staining, the histomorphological changes were studied in both Normotensive and Hypertensive groups. Results:The number of villous capillaries was increased in hypertensive group. The quantitative difference between number of villous capillaries in normal and hypertensive groups was statistically significant. Conclusion: Increased number of villous capillaries was observed in (H) group as compared to (N) group that may be the cause or effect of placental hypoxia.